PENYELESAIAN SENGKETA WILAYAH DARAT ANTARA INDONESIA DENGAN TIMOR LESTE DI WILAYAH NAKTUKA MENURUT PERSPEKTIF HUKUM INTERNASIONAL: Settlement Of Land Area Disputes Between Indonesia And Timor Leste In Naktuka Region Under Internasional Law Perspective - Nugroho, Abhyasa Shidqi; Permanasari, Arlina (AMICUS CURIAE, 2024)
The territorial dispute between Indonesia and Timor Leste began in 2009. This was caused by Timor Leste's unilateral declaration of ownership rights to Naktuka with an area of ​​1069 hectares (ha). The formulation of the problem is what is the legal status of the Naktuka Region and its interpretation based on the Provisional Agreement between Indonesia and Timor Leste in 2005. This type of research uses normative research, is descriptive in nature, secondary data and primary data are analyzed qualitatively and the method of drawing conclusions uses deductive logic. Based on the results of the research that many efforts were made by Indonesia and Timor Leste in resolving the Naktuka Territory dispute which had been regulated by International Law and Peace were included in the joint agreement and the 1969 Vienna Convention contained in article 31 Paragraph 1 an agreement must be interpreted in good faith, meaning every international treaty needs to have a certain understanding of its scope, content and relevance. In this case what the researcher means is the legal implementation of the 1969 Vienna Convention with the use of the Naktuka Territory by Timor Leste and Indonesia.